Importance of Student-Centred Learning Strategy in Developing English Speaking and Writing Competence at the Elementary Level of EBC. Seloi-Craic, Aileu, Timor-Leste - Magno Ximenes, Salvador; da Costa, Victor (Journal of Information System and Education Development, 2025)
This article discusses the importance of student-centred learning (SCL) strategies for enhancing students’ ability to learn English and their speaking and writing competence at the elementary level in Timor-Leste. The research employed a qualitative design to investigate how teachers focus on SCL strategies to enhance students' language skills and how these strategies are implemented in classroom practice, based on semi-structured interviews with one English teacher and three students at EBC Seloi-Craic in Aileu. Thematic analysis was used to analyse the data, which included the participants' perceptions and experiences. The results indicate that the teacher focused on SCL and included systematic tasks like quizzes, dictations, sentence constructions, and classroom presentations, which gave the students opportunities to express their thoughts. Collaborative learning, differentiated assessment, and motivation support could promote students' confidence, fluency, engagement, critical thinking, creativity, and collaboration. Students attested that SCL provided a supportive classroom atmosphere in which they felt free to communicate and learn from fellow pupils. The research finds that SCL is a useful pedagogy that can be successfully used to enhance English language proficiency in multilingual settings like Timor-Leste, and it has implications for teaching practice, curriculum, and teacher development